City landscape and environs : a cultural ecological perspective - Gupta, G.P. (Jaipur, 1989)
The text is organized around four major themes : cultural area, cultural ecology, cultural integration and cultural landscape. In addition to these, a number of other elements have also been discussed. The author has also made quite useful suggestions for the attention of relational development b authorities. The study lights up a new path not only for cultural and urban geographers of India but rural development planners with whose disciplines it has extensive and deep interfaces.
Keywords: Human ecologystudy and teaching